Vrednovanje zvučnih okolina s obzirom na nagle i neočekivane promjene zvuka : doktorski rad - Suhanek, Mia; Đurek, Ivan (Zagreb : M. Suhanek ; Fakultet elektrotehnike i računarstva, 2013)
SAŽETAK: Cilj provedenog istraživanja je definirati i prikazati metodu vrednovanja zvučnih okolina u ovisnosti o objektivnim akustičkim parametrima. Istraživanje je provedeno na četiri tipične urbane zvučne okoline te se sastoji od dva dijela: zadatka koji izvršavaju slušatelji dok im se reproducira određena zvučna okolina i upitnika koji rješavaju, a prilagođen je za svaku zvučnu okolinu. Na temelju rezultata zadatka daje se zaključiti kako nagle i neočekivane promjene u glasnoći utječu na koncentraciju slušatelja, dok se analizom upitnika dolazi do relevantnih parova atributa za zvučne okoline te razloga zašto je pojedini kratki zvučni signal ometajući. Definirani parovi atributa te rezultati obavljanja zadatka tijekom reprodukcije zvučnih okolina su subjektivni akustički parametri kod vrednovanja samih zvučnih okolina. Korištenjem isključivo subjektivnih akustičkih parametara ne može se dovoljno kvalitetno opisati zvučnu okolinu niti dati potpuni smisao i vrijednost faktoru ometanja (koji je direktna posljedica naglih i neočekivanih promjena u glasnoći zvučne okoline, ali i same "prirode" zvučne okoline). Iz tog razloga, napravljena je sinteza subjektivnih parametara te subjektivnih ispitivanja s postojećim i novim, objektivnim akustičkim parametrima. Novi, objektivni parametri karakteristični isključivo za zvučne okoline dobiveni su dodatnim istraživanjem u kojem su kratki zvučni signali "ubačeni" u najugodniju zvučnu okolinu opisanu već navedenim relevantnim parovima atributa. Za vrijeme trajanja reprodukcije, slušateljima je dana mogućnost podešavanja glasnoće, trajanja i brzine porasta kratkih zvučnih signala. Na kraju, sintezom svih rezultata, dobiven je model za procjenu faktora ometanja koji je zatim potvrđen na "novoj" zvučnoj okolini, nezavisnoj od prijašnjih ispitivanja. Važno je naglasiti da su se u svim istraživanjima poštovali metodologija i postulati psihologije i statistike, jer u protivnom zaključke dokazane na reprezentativnom uzorku ne bi bilo moguće primijeniti na populaciju. - KLJUČNE RIJEČI: akustička kategorizacija, zvučna okolina, objektivni akustički parametri, subjektivni akustički parametri, parovi atributa, t-test, χ²-test, ANOVA, faktor ometanja
SUMMARY: The aim and purpose of this thesis is to investigate the impact of sudden and unexpected loudness changes, compared to the average loudness of a soundscape, on people's concentration and change in perception. The doctoral hypothesis had been based on my own observations and experiences. A matter of adapting to a certain soundscape, if it is not too loud, but noticing distraction caused by sudden and unexpected loudness changes while performing concentration demanding tasks has proven to be an interesting study. A real question was how individual sounds, which in a certain way "do not belong" in a specific soundscape, determine how the complete soundscape could be perceived as pleasant or unpleasant and whether the sound that was not expected, even if it were relatively quiet, distracted or even disturbed us in comparison to the soundscape that we had became accustomed to. Therefore, the idea is to study different soundscapes while focusing on sudden and unexpected loudness changes. The dissertation research participants were tested by performing a “task” which had been constructed in a way to substitute people’s everyday tasks which require a minimal level of concentration. The subjects were performing this task while listening to various soundscape recordings.The study had been carried out with natural sounds (natural soundscapes) and as a result certain objective parameters were determined that form the soundscape evaluation model used for estimating the soundscape pleasantness or similarly the soundscape unpleasantness. A classification of attributes describing the subjective experience of a soundscape had also been carried out. The results showed which of the attributes are relevant to adequately describe a soundscape and to define new objective parameters determining the distraction factor of a certain soundscape. Most importantly, a model which calculates the distraction factor had been established and then confirmed on an uninvestigated and independent soundscape. The second dissertation chapter clarifies the concept of a soundscape, the most common classification of soundscapes, recording methodology and potential analysis, while also describing all selected and recorded soundscapes. The third and fourth chapters deal with parameters most commonly used for describing and evaluating soundscapes. Chapter three describes the objective acoustic parameters while chapter four deals with the subjective parameters specific to the evaluation and classification of soundscapes. The fifth chapter presents a detailed analysis and the statistical processing of the obtained results, while the sixth chapter describes further research with short sound signals (by previous studies described as distracting and annoying) that were inserted into the most pleasant soundscape (proven by previous studies) and finally the analysis of the related results. The aforementioned analysis shows the most common reasons why a certain sound would be perceived as annoying and distracting. A synthesis of the results of subjective tests and objective acoustic parameters had been carried out in the seventh chapter. The eighth chapter describes the development of the model used for calculating the distraction factor of a soundscape and the model testing on a "new", independent soundscape. It is important to emphasize that the methodology and respected postulates of psychology and statistics were fully complied with in all the research, whereas otherwise the findings proven on a representative sample could not be applied to the population. - KEYWORDS: acoustical categorization, soundscape, objective acoustic parameters, subjective acoustic parameters, attribute pairs, t-test, χ²-test, ANOVA, distraction factor
Na spor. nasl. str. naslov na eng. jeziku: Evaluation od soundscapes regarding sudden and unexpected sound changes : doctoral thesis
Bibliografija: 146-147 str. - Sažetak na eng. i hrv. jeziku. - Životopis [uključuje popis objavljenih radova autorice]